The Zero Trust Security Model and Cybersecurity in the Industries - Mylavarapu, Suchaye (Journal of Student Research, 2024)
This paper aims to highlight the critical importance of cybersecurity in safeguarding against the ever-evolving and sophisticated nature of cyber threats that have become the norm nowadays. It is specifically pointed out that healthcare organizations must prioritize data management and robust security measures to combat ransomware and data breaches. At the same time, the software industry faces cybersecurity challenges due to the vulnerability of interconnected systems. Organizations must take proactive steps to identify potential threats and vulnerabilities and be prepared to handle any security incidents. Additionally, companies should ensure that their employees are educated on the necessary security measures to protect their data and systems. Consequently, security and development practices, software delivery, threat management, and incident management are vital for defense against cyberattacks. To protect digital assets and data, the analysis delves into firewalls, encryption, access controls, and other cybersecurity measures. Companies should also provide training to their employees on best security practices and regularly update their systems with the latest security patches. Additionally, they should develop a security policy to ensure safe access and use of the company’s digital assets. Moreover, the zero-trust concept has been introduced as an advanced cybersecurity framework that challenges traditional security frameworks. Overall, this paper hopes to emphasize the importance of cybersecurity in various industries, specifically in the. healthcare, software, and the film industries are very important in safeguarding individuals, organizations, systems, assets, and information from threats.